MATCHING AND RESEARCH FOR VOTER DATA UPDATE IN SURABAYA MAYORAL ELECTION IN 2020 FROM THE PERSPECTIVE OF FIQH AL-SIYASAH - Musyafaah, Nur Lailatul; Rhomandana, Rizal Dwi; Nisa, Nabila Khoirun; Sofyan, Alfin (JURNAL SULTAN: Riset Hukum Tata Negara, 2023)
During Covid-19 Pandemic, the election in Indonesia was still carried out. However, there had previously been a withdrawal of the schedule. Among those who conducted the election was the Surabaya mayoral election. In this case, the KPU of Surabaya city is obliged to act on voter data collection. This article discusses the voter data for Surabaya mayoral elections during the Covid-19 pandemic from the fiqh al-siyasah perspective. The research is field research with qualitative data processing. Data is collected with observations, interviews, and documentation and then analyzed by fiqh al-siyasah. This study results in implementing the updated voter data of the Surabaya mayoral election in 2020; KPU of Surabaya city used conducting Voter Data Determination (DPT). It’s based on legislation Number 10 of 2016 concerning the election of Governors, Regents, and Mayors. Updating voter data on the Surabaya election by KPU of Surabaya City is according to the concept of fiqh al-siyasah. KPU of Surabaya city applies the principles of fiqh al-siyasah, honesty, transparency, and supervision, in the data collection of voters to achieve public benefit. This is according to the concept of tasharruf al-imam ‘ala al-ra’iyyah manuth bi al-mashlahah (the leader’s policy on people must align with the public interest).